A hundred species, mostly new—first assessment of ribbon worm diversity and distribution in Oman - Maslakova, Svetlana; Cherneva, Irina; Kahn, Ethan; Wong, Audrey; Paulay, Gustav (PeerJ, 2025)
Background Biodiversity is a key characteristic of any ecosystem but remains largely undescribed for most marine animals. Ribbon worms (phylum Nemertea), a diverse but poorly sampled phylum ubiquitous in the world’s oceans, are a case in point. Aside from their function as predators in marine communities, nemerteans are biomedically relevant because they produce diverse toxins, and some impact bivalve, decapod, and glass eel fisheries. Identification of nemerteans is challenging because many species look alike. The task is further complicated by many descriptions being based on preserved specimens, and therefore lacking characters of external appearance of live specimens. Characters of internal anatomy form the basis of traditional systematics but are more recently shown to be of little use in distinguishing between closely related species. This makes DNA data essential in species descriptions, and assessments of diversity and distribution. Methods In a first modern survey of the phylum in Arabian waters, we collected nemerteans from a variety of habitats, focusing sampling on hard-bottom substrata, especially coral reefs. Specimens were triple-documented with photos, morphological vouchers, and DNA barcodes. Species delineation was based on morphology and Cytochrome Oxidase I sequences. Sequences and associated data are deposited in public databases, and vouchers at the Florida Museum of Natural History. Results We documented 107 nemertean species in Oman, where none were previously known. This doubles the number of genetically characterized nemertean species for the entire Indo-West Pacific—a testament to how poorly sampled the phylum is in the most biodiverse marine region of the world. As many as 98% of the species were undescribed, and 93% are not documented outside Arabia. Half of the species were rare, and most—cryptic. Undescribed species were assigned unique alphanumeric temporary names for tracking in the literature and public databases. Estimates of source diversity suggest that future surveys might uncover an additional ∼200 species by including other locations and types of habitats, particularly soft bottoms, and the water column. Little overlap was observed between species found in the northern (Gulf of Oman) and southern (Sea of Arabia) regions, and many that occurred in both areas showed evidence of genetic differentiation corresponding to the major biogeographic break at R’as-al-Hadd. Conclusions The high diversity, novelty, and distinctiveness of this fauna underscore the importance of sampling the most biodiverse and least studied tropical marine regions of the world. The large amount of cryptic and undescribed diversity highlights the critical role of DNA barcodes and rapid approaches to species descriptions.
Keywords: Taxonomy; Nemertea; Distribution; Species diversity; Temporary names; Arabia; Oman